Effects of total temporomandibular joint replacement with alloplastic prosthesis – a systematic review - Pär Morin; Jani Talvilahti; Mattias Ulmner; Per Alstergren; Eva Nordendahl; Aron Naimi- Akbar (Acta Odontologica Scandinavica)
Objectives: This paper studies the treatment effect of total joint replacement (TJR) of the temporomandibular joint (TMJ) with alloplastic joint prosthesis regarding function, symptoms and health-related quality of life compared to other surgical and non-surgical treatments in patients with TMJ disorders.